Manfaat Konsumsi Kopi dalam Meningkatkan Kemampuan Mengingat (Memori): A Narrative Review - Adelina Elsa Damayanti; Bambang Wirjatmadi; Sri Sumarmi (Media Gizi Kesmas, 2023)
Background: The ability to remember (memory) is one of the cognitive functions which is the ability to encode, store, retain and remember information or past experiences or something that happened to the human brain. Most of this information is stored for future control of motor activity and for use in thought processing. Coffee is one of the most popular drinks by people around the world. Coffee contains many antioxidants which are believed to improve one of the cognitive functions, which is memory. In recent years several studies have shown that coffee consumption can bring health benefits by affecting many biological systems, among which it has been shown that people who drink coffee regularly have a lower risk of developing Diabetes Mellitus Type 2, colon cancer, and liver cirrhosis. Because of these benefits, coffee can now be classified as a functional food. Objective: The purpose of this study was to determine the benefits of coffee on the ability to remember (memory). Discussion: From several studies that had been done previously, it is known that coffee can significantly improve memory. Conclusion: Coffee contains many antioxidants that can help improving memory. It is hoped that in the future there will be more research that can explain in more detail how coffee can improve or repair cognitive functions such as memory, considering that coffee is one of the drinks that is widely consumed by people in the world and is consumed by almost everyone.